Kirlianographic investigation of the anthropogenic factors influence on biota - M. V. Kurik; L. A. Pesotskay; N. V. Glukhova; L. R. Nikogosyan (Journal of Education, Health and Sport, 2017)
Kurik M. V., Pesotskay L. A., Glukhova N. V., Nikogosyan L. R. Kirlianographic investigation of the anthropogenic factors influence on biota. Journal of Education, Health and Sport. 2017;7(1):359-368 eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.268736